Shear strength (handheld penetrometer) from IODP Hole 386-M0088B - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Shear strength from handheld penetrometer of the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). This dataset was obtained at the end of the core processing workflow during the third phase (Personal Sampling Party, PSP) of expedition 386, which took place between 2022-11-15 – 2022-11-30 onboard D/V Chikyu. Measurements were performed on the work halves of core sections using a handheld (pocket) penetrometer equipped with a 10 mm diameter tip. The tip was pushed 6.3 mm perpendicular to the split core surface with the measuring pin downward until the groove marked on the tip was even with the level of the core surface. The resulting resistance (compressive strength) was read from the device and used to calculate undrained shear strength. At each measurement depth, three measurements were conducted and the resulting undrained shear strength averaged. In the case of major discrepancies between the three measurements, the team verified the results by repeating the measurements. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023